(untitled) (Med Phoenix, 2024)
Introduction: Adverse drug reactions and its underreporting exists globally so this study was conducted to know the factors which affected medical doctors from reporting at National Medical College and Teaching Hospital (NMCTH), Birgunj, Nepal. Materials and Methods: A descriptive cross-sectional study was conducted among clinical doctors. Self-administered questionnaire tool was used for the collection of data. The questionnaire consisted of demographic status, factors encouraging ADR reporting and factors discouraging ADR reporting. The distributive statistics like frequency and percentage were used for evaluation of the data. Results: The response rate was 88.51% and most of the participants were male (61.24%). Serious reactions encouraged about 96.06% of medical doctors whereas unusual reactions encouraged 94.94% of medical doctors. New products encouraged about 98.31% of medical doctors. The percentage of doctors not knowing how to fill and report adverse drug reaction was 76%. Constrainment of time to fill the form percentage was 64%. The percentage of medical doctors who agreed that a report will generate an extra work was 69%. Not reporting because no incentives percentage was 64%. Belief that only safe drugs are marketed 58%. Conclusion: The study revealed that adverse drug reporting system is still in preliminary stages so timely training, seminars, inclusion in undergraduates about its importance should be done so create a positive attitude towards adverse drug reporting.